Development of mathematics learning modules with PBL models on the metacognitive skills of students - Nina Ardianti Dewi; Waminton Rajagukguk; Rosmala Dewi (Inovasi Kurikulum, 2024)
The teaching materials used do not facilitate students' metacognitive skills, causing students' metacognitive skills to be low. The research aims to produce products in the form of valid, practical, and effective learning modules on the metacognitive skills of grade V students. Teaching materials are developed using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research developed Mathematics teaching materials with PBL models for grade V elementary school students. The subjects of this study were grade V students of SD Negeri 060874 Medan, which consisted of 27 students. Teaching materials that have been developed meet the validity criteria shown by using validation sheets on aspects of material, language, and design, with each aspect with very valid categories. The teaching materials developed also meet the practical criteria indicated by the questionnaire response given to students after the application of teaching materials with the criteria obtained is very practical. Furthermore, the teaching materials developed also meet the effective criteria, this is shown from the results of the comparison of Pre-test and Post-test tested with N-Gain with the acquisition of N-Gain scores, metacognitive skill questionnaires, and student learning outcomes with moderate categories with effective criteria.   Abstrak Bahan ajar yang digunakan kurang memfasilitasi keterampilan metakognitif siswa sehingga menyebabkan keterampilan metakognitif siswa rendah. Tujuan dari penelitian adalah untuk menghasilkan produk berupa modul pembelajaran yang valid, praktis dan efektif terhadap keterampilan metakognitif siswa kelas V. Jenis penelitian yang dilakukan adalah penelitian pengembangan Research and Development (R&D). Bahan ajar dikembangkan dengan menggunakan model pengembangan ADDIE yang terdiri dari lima tahapan yaitu Analysis, Design, Development, Implementation dan Evaluation. Penelitian ini mengembangkan bahan ajar Matematika dengan model PBL untuk siswa kelas V siswa Sekolah Dasar. Subjek penelitian ini merupakan siswa kelas V SD Negeri 060874 Medan yang terdiri dari 27 siswa. Bahan ajar yang telah dikembangkan memenuhi kriteria kevalidan yang ditunjukkan dengan menggunakan lembar validasi pada aspek materi, Bahasa dan desain dengan masing-masing aspek dengan kategori sangat valid. Bahan ajar yang dikembangkan juga memenuhi kriteria praktis yang ditunjukkan dengan angket respons yang diberikan kepada siswa setelah penerapan bahan ajar dengan kriteria yang diperoleh adalah sangat praktis. Dan bahan ajar yang dikembangkan juga memenuhi kriteria efektif hal ini ditunjukkan dari hasil perbandingan Pre-test dan Post-test yang diuji dengan N-Gain dengan perolehan skor N-Gain angket keterampilan metakognitif dan hasil belajar siswa dengan kategori sedang dengan kriteria efektif. Kata Kunci: bahan ajar; keterampilan metakognitif; Matematika; PBL